946. Risk factors and Metabolic Implications of Integrase Inhibitor Associated Weight Gain. (31st December 2020) - Asundi, Archana; Olson, Alex; Jiang, Wenqing; Patel, Swati; White, Laura F; Sagar, Manish; Lin, Nina H
Abstract: Background: Excessive weight gain associated with integrase strand transfer inhibitor (InSTI) antiretrovirals is an emerging issue in the current antiretroviral treatment (ART) era. Despite the known association between excess weight and impaired glucose tolerance in the general population, the metabolic implications of InSTI-associated weight gain have not been established. The objective of this study was to evaluate the presence of InSTI-associated weight gain amongst a diverse, urban population and to investigate potential risk factors and metabolic implications. Methods: We obtained demographic, pharmacy and laboratory data from the hospital clinical data warehouse for ART-naïve adult HIV+ patients at Boston Medical Center between fiscal year (FY) 2007-2017. We compared patients who initiated on an InSTI to those with an alternate regimen (i.e. PI, NNRTI) who remained on their initial regimen for at least 18 months. Individuals with diabetes mellitus (DM) prescription or ICD 9/10 code prior to ART initiation were excluded. Our primary outcome was percent weight change in the first 24 months of ART estimated by linear mixed effects model fit by restricted maximum likelihood. Our secondary outcome was incident DM diagnosis in the 18 months after ART using progression-free survival (PFS). PFS rates were estimated by the Kaplan-Meier method and log-rank test, and Cox proportional-hazards model were determined, all using R v3.6.2. Results: Between FY 2007-2017, 139 patients were initiated on InSTIs and 1117 were initiated on alternative anchor regimens. Approximately, one third of the cohort was female and more than 75% were non-white. InSTI use in women was associated with increased weight gain in the first 24 months of ART compared to non-InSTIs (+9.57%, p = 0.002, Figure 1 ). InSTI use was associated with more incident DM diagnoses in the first 18 months of ART compared to non-InSTI regimens (HR = 3.27, p = 0.014). Figure 1: Percentage weight change from baseline at ART initiation between InSTI and non-InSTI regimens Conclusion: Females have higher InSTI-associated weight gain which suggests they may be more susceptible to adverse metabolic issues. InSTI use appears to be associated with an increased incidence of DM diagnoses following ART initiation. Further prospective and controlled studies will be necessary to describe the mechanism of this effect and refine HIV management strategies. Disclosures: Archana Asundi, MD, Gilead (Scientific Research Study Investigator)Merck (Scientific Research Study Investigator)ViiV (Scientific Research Study Investigator) Nina H. Lin, MD, Gilead Sciences (Scientific Research Study Investigator)ViiV (Scientific Research Study Investigator)